Coordinated Regulation of Protoperithecium Development by MAP Kinases MAK-1 and MAK-2 in Neurospora crassa - Lan, Nan; Ye, Shuting; Hu, Chengcheng; Chen, Zhiling; Huang, Jun; Xue, Wei; Li, Shaojie; Sun, Xianyun (Frontiers in Microbiology, 2021)
MAP kinase pathways function as signaling hubs that are integral for many essential cellular processes, including sexual development. The molecular mechanisms of and cross talk between PR and CWI MAP kinases pathways have been extensively studied during asexual development. However, if these can be extended to sexual development remains elusive. By analyzing genome-wide transcriptional responses to deletion of each of two MAP kinase coding genes mak-2 (PR-MAP kinase pathway) and mak-1 (CWI-MAP kinase pathway) in Neurospora crassa during protoperithecium formation, 430 genes co-regulated by the MAK-1 and MAK-2 proteins were found, functionally enriched at integral components of membrane and oxidoreductase. These genes include 13 functionally known genes, participating in sexual development (app, poi-2, stk-17, fsd-1, vsd-8 and NCU03863) and melanin synthesis (per-1, pkh-1, pkh-2, mld-1, scy-1, trn-2 and trn-1), as well as a set of functionally unknown genes. Phenotypic analysis of deletion mutants for the functionally unknown genes revealed that 12 genes were essential for female fertility. Among them, single gene deletion mutants for NCU07743 (named as pfd-1), NCU02250 (oli) and NCU05948 (named as pfd-2) displayed similar protoperithecium development defects as the ∆mak-1 and ∆mak-2 mutants, failing to form protoperithecium. Western blotting analysis showed that both phosphorylated and total MAK-1 proteins were virtually abolished in the ∆nrc-1, ∆mek-2 and ∆mak-2 mutants, suggesting that the posttranscriptional regulation of MAK-1 is dependent on the PR MAP kinase pathway during the protoperithecium development. Taken together, this study revealed the regulatory roles and cross talk between PR and CWI MAP kinase pathways during protoperithecium development.